Urban Commons on Uncommon Ground: Experimenting With Co-Governance in China's Global Cities - Guanchi Zhang (Washington University Global Studies Law Review, 2025)
Urban centers worldwide, including those in the U.S. and China, are powerhouses of wealth and opportunity yet suffer from increasing unaffordability and exclusivity. This begs the question: Can land use regulations be the key to making our urban environments prosperous and common? This paper navigates the growing discourse surrounding urban commons, which is a concept that views urban land as a shared resource, with individual usage influencing comprehensive economic and social outcomes for the community. The discourse moves beyond the traditional, growth-centric approach favoring the “optimal use” of land and contrasts it with an emerging co-governance paradigm. This alternative model encourages an equitable distribution of power and interests among communities, governments, and developers through systematic collective action. Building upon the urban commons discussion in the context of the U.S., this paper turns its gaze toward urban China. In a landscape marked by shifting state-society relations, economic upheaval, and rising demands for equitable property rights, China provides a compelling backdrop. Through extensive fieldwork and analysis of historical, legal, and policy documents, this paper offers a ground-level perspective of China’s pioneering foray into co-governance. This venture places indigenous neighborhoods and villages at the center of land redevelopment, empowering community members to negotiate with developers and local governments from a position of strength. It also allows for collective decision-making on future land development and thus harnesses the shared value that state-corporate alliances could lose or monopolize. Despite these advancements, challenges persist. Intensified social conflicts and the uneven landscape of community power expose the vulnerability of communities facing deep-rooted pro-growth inclinations. This paper advocates for striking a balance between short-term power sharing and long-term institutions that regularize collective action. Such an approach is critical to the paradigm shift towards commonality and prosperity in urban development. As such, this paper promises to offer a wealth of actionable insights for legal scholars and urban policymakers in both China and the U.S.
Keywords: urban commons; urban land use; community land governance; equitable land use; china; land use policy; urban collective action; state-society relations